The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1126/scirobotics.aan2971
|View full text |Cite
|
Sign up to set email alerts
|

On prosthetic control: A regenerative agonist-antagonist myoneural interface

Abstract: The agonist-antagonist myoneural interface enables bidirectional signaling for enhanced prosthetic control and sensation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
66
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 34 publications
5
66
0
1
Order By: Relevance
“…Graded afferent signals were then recorded from the agonist muscle's innervation nerve during closed-loop functional electrical stimulation of the antagonist, demonstrating the capacity of the AMI to provide natural proprioceptive feedback. In another murine study, we demonstrated that a functional AMI could be constructed from small denervated and devascularized muscle grafts placed in the vicinity of transected motor nerves (40). A caprine experiment further validated that the principles demonstrated in (39) are scalable to larger animal models (41).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Graded afferent signals were then recorded from the agonist muscle's innervation nerve during closed-loop functional electrical stimulation of the antagonist, demonstrating the capacity of the AMI to provide natural proprioceptive feedback. In another murine study, we demonstrated that a functional AMI could be constructed from small denervated and devascularized muscle grafts placed in the vicinity of transected motor nerves (40). A caprine experiment further validated that the principles demonstrated in (39) are scalable to larger animal models (41).…”
Section: Introductionmentioning
confidence: 82%
“…Research is already underway to explore construction of AMIs at other amputation levels, as well as in the upper extremity. A recent study demonstrated the potential to leverage regenerative capabilities of nerve and muscle tissue in the construction of AMIs in settings where distal tissues are no longer available, such as traumatic amputations or revisions to existing amputations (40). It is worth noting that, even with these advancements, the implementation of the AMI may not be appropriate in patients requiring amputation due to advanced peripheral vascular disease.…”
Section: Of 13mentioning
confidence: 99%
“…9 Particularly, various wearable epidermal bioelectronic devices have been commercialized and routinely used for diverse clinical purposes. 10 Miniaturized implantable devices have driven breakthroughs in treatments for neurological disorders and damage including deep brain stimulation probes for Parkinson's disease [11][12][13] and essential tremors, 14 neural interfaces for robotic prostheses, [15][16][17][18] flexible electrode arrays for heart failures, 9,19,20 and closed-loop electrode arrays for spinal cord injuries. 21,22 Despite remarkable advances in the recent few decades, the intrinsic differences between biological tissues and man-made electronics pose immense challenges in materials, design, and manufacturing of the next generation bioelectronics.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic relationships within agonist–antagonist muscle pairs in a limb are also fundamental for creating a natural sensation of joint movement [ 26 ] since this connection engages the related proprioceptors. During a typical amputation procedure, muscle tissues in the residual limb are placed isometrically severing the dynamic connection between agonist–antagonist muscle pairs, which limits the ability of the muscles to provide meaningful proprioceptive feedback [ 27 ].…”
Section: Introductionmentioning
confidence: 99%